The end of the American century? Slow erosion of the domestic sources of usable power. (1st May 2019) - Trubowitz, Peter; Harris, Peter
Abstract: Can the United States continue to shape international politics as it has done for the past 70 years, or is the era of US preponderance coming to an end? Most attempts to answer this question focus on the concept of relative power—that is, the balance of material capabilities between the US and its geopolitical competitors. From this perspective, the 'American era' will be over when rival powers are able to muster the military capability to counteract US ambitions on the world stage. In this article, we argue that the most pressing checks on US leadership come not from foreign competitors, but rather from domestic politics. While America's relative power as measured by its military arsenal vis-à-vis those of its rivals has held steady, its 'usable power' has declined. We attribute this decline in usable power to three domestic-level factors: the emergence of hyper-partisanship, the absence of a compelling strategic narrative, and the erosion of a social contract of inclusive growth. Our analysis suggests that US leaders will find it difficult to implement a programmatic grand strategy of any description—liberal internationalism, offshore balancing, retrenchment or even President Trump's 'America First' strategy—so long as domestic-level dysfunction goes unattended and until usable power is restored.